Use of anaerobic culture for the improved isolation of Streptococcus pneumoniae. Issue 1 (January 1976) - Howden, R
Abstract : The following report compares the results of aerobic and anaerobic cultivation for the primary isolation of Streptococcus pneumoniae (the pneumococcus) from the respiratory tract of children. Of 414 specimens of respiratory tract secretions cultured, 65 (15-7%) yielded pneumococci; 31 (47-7%) grew both aerobically and anaerobically, but 34 (52-3%) strains were isolated only from the anaerobic culture. Pneumococci cultured anaerobically with added carbon dioxide characteristically produce large mucoid colonies which are more easily distinguished than the 'normal' colonies commonly seen in the mixed flora isolated from respiratory sites. This advantage justifies the inclusion of anaerobic culture when attempting to isolate Str. pneumoniae from clinical material.